Advances in accounting behavioral research. Vol. 8 - Arnold, Vicky (Advances in accounting behavioral research,, 2005)
Advances in Accounting Behavioral Research publishes quality articles encompassing all areas of accounting that incorporate theory from and contribute knowledge and understanding to the fields of applied psychology, sociology, management science, and economics. The series promotes research that integrates accounting issues with organizational behavior, human judgment/decision making, and cognitive psychology. Volume 8 contains papers on a variety of behavioral accounting topics. The lead article is a literature review of research associated with the belief adjustment model (Hogarth and Einhorn 1992), which has been used as the theoretical support for a significant body of research in accounting. This article synthesizes prior accounting research and identifies future research opportunities. The remaining eight articles are empirical in nature and examine behavioral issues in auditing, ethics, and management accounting. One study investigates the efficiency and effectiveness of a recent change to the audit workpaper review process, which delegates more review tasks to senior and staff auditors. Two studies investigate communications in the audit review process with one focusing on linguistic delivery style of the client and the other focusing on electronic communication medium for client inquiry. Another study investigates the concept of role morality and whether accountants have different ethical propensities when making business decisions rather the personal decisions. The remaining four articles investigate various aspects of managerial accounting systems, including budgetary participation, the role of culture and acculturation in information sharing, activity based costing, and manager's moral equity. Overall, these papers provide interesting insight into various aspects of behavioral accounting.